DISCOVERY LEARNING MODEL FOR IMPROVING THE STUDENTS’ CRITICAL THINKING SKILLS: A NARRATIVE REVIEW - Eni Kurniawati; Ahwy Oktradiksa; Norma Dewi Shalikhah (Al-Bidayah : jurnal pendidikan dasar Islam, 2021)
The learning model used in primary schools still tends to use conventional learning, resulting in less optimal critical thinking skills and students’ learning outcomes. This study aims to analyze the discovery learning model in improving critical thinking skills and learning outcomes of primary school students. This study uses a narrative review with 2 steps, namely database search, and thematic analysis. The criteria used are articles from national and international scientific journals, articles related to research topics, articles published in the last 5 years with a duration (2016-2021), and articles available full-text pdf versions that have been published on Google Scholar and Research gate. Of the 28 articles obtained, only 25 articles are analyzed. The results of this study indicate that the discovery learning model can improve critical thinking skills and learning outcomes of primary school students.